Analogues of a Cyclic Antimicrobial Peptide with a Flexible Linker Show Promising Activity against Pseudomonas aeruginosa and Staphylococcus aureus - Thomas T. Thomsen; Helen C. Mendel; Wafaa Al-Mansour; Alberto Oddo; Anders Løbner-Olesen; Paul R. Hansen (MDPI AG, 2020)
The emergence of multi-drug resistant bacteria is becoming a major health concern. New strategies to combat especially Gram-negative pathogens are urgently needed. Antimicrobial peptides (AMPs) found in all multicellular organisms act as a first line of defense in immunity. In recent years, AMPs have attracted increasing attention as potential antibiotics. Naturally occurring antimicrobial cyclic lipopeptides include colistin and daptomycin, both of which contain a flexible linker. We previously reported a cyclic AMP BSI-9 cyclo(Lys-Nal-Lys-Lys-Bip-O2Oc-Nal-Lys-Asn) containing a flexible linker, with a broad spectrum of activity against bacterial strains and low hemolytic activity. In this study, improvement of the antimicrobial activity of BSI-9, against the European Committee on Antimicrobial Susceptibility Testing (EUCAST) strains of S. aureus, E. coli, A. baumannii, and P. aeruginosa was examined. This led to synthesis of eighteen peptide analogues of BSI-9, produced in four individual stages, with a different focus in each stage; cyclization point, hydrophobicity, cationic side-chain length, and combinations of the last two. Specifically the modified compound 11, exhibited improved activity against Staphylococcus aureus and Pseudomonas aeruginosa with MIC of 4 µg/mL and 8 µg/mL, respectively, compared to the original BSI-9, which had an MIC of 16-32 µg/mL.